1995
DOI: 10.1038/374546a0
|View full text |Cite
|
Sign up to set email alerts
|

CpG motifs in bacterial DNA trigger direct B-cell activation

Abstract: Unmethylated CpG dinucleotides are more frequent in the genomes of bacteria and viruses than of vertebrates. We report here that bacterial DNA and synthetic oligodeoxynucleotides containing unmethylated CpG dinucleotides induce murine B cells to proliferate and secrete immunoglobulin in vitro and in vivo. This activation is enhanced by simultaneous signals delivered through the antigen receptor. Optimal B-cell activation requires a DNA motif in which an unmethylated CpG dinucleotide is flanked by two 5' purine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

44
2,422
9
24

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 3,256 publications
(2,499 citation statements)
references
References 28 publications
44
2,422
9
24
Order By: Relevance
“…[6][7][8] It appears that such cytokines activate the immune system and induce strong antitumor effects in mice. 4,5 On the other hand, Li et al have shown that such cytokines, which are secreted after intravenous injection of lipoplexes, can be toxic and cause short-term gene expression and refractory behavior on repeated dosing at frequent intervals.…”
Section: Increases In the Liver And Spleen After Lipoplex Injection Amentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] It appears that such cytokines activate the immune system and induce strong antitumor effects in mice. 4,5 On the other hand, Li et al have shown that such cytokines, which are secreted after intravenous injection of lipoplexes, can be toxic and cause short-term gene expression and refractory behavior on repeated dosing at frequent intervals.…”
Section: Increases In the Liver And Spleen After Lipoplex Injection Amentioning
confidence: 99%
“…6,24 Therefore, we first examined the biodistribution of a 32 P-lipoplex after intravenous administration in saline-pretreated and GdCl 3 -pretreated mice. Mice received intravenous injections of a GdCl 3 solution or saline 24 h before lipoplex administration.…”
Section: Increases In the Liver And Spleen After Lipoplex Injection Amentioning
confidence: 99%
“…Finally, we wish to stress that although these innate immune responses might appear to limit the use of mRNA for non-immunotherapy applications, as evidenced by the fact that clinical IVT mRNA-therapy is still very much in its infancy, these responses do not solely occur in response to mRNA. Long before the discussion of mRNA-induced immune triggering arose, we knew about TLR9 ligation of CpG-rich pDNA, also resulting in the secretion of type I IFN and IL-12 [147][148][149].…”
Section: Discussionmentioning
confidence: 99%
“…46 For example, bacterial DNA has been shown to cause activation and induction of inflammatory genes in B lymphocytes and NK cells. [47][48][49] A comparison of helper-dependent Ads comprised of HPRT or lambda DNA stuffer fragments revealed that the HPRT DNA containing vector performed best. A possible reason suggested for the differences in the cellular response to foreign DNA was related to differences in DNA methylation and/or base composition.…”
Section: Discussionmentioning
confidence: 99%